Calcium binding of the antifungal protein PAF: Structure, dynamics and function aspects by NMR and MD simulations - Fizil, Ádám; Sonderegger, Christoph; Czajlik, András; Fekete, Attila; Komáromi, István; Hajdu, Dorottya; Marx, Florentine; Batta, Gyula (PLOS ONE, 2018)
Calcium ions (Ca2+) play an important role in the toxicity of the cysteine-rich and cationic antifungal protein PAF from Penicillium chrysogenum: high extracellular Ca2+ levels reduce the toxicity of PAF in the sensitive model fungus Neurospora crassa in a concentration dependent way. However, little is known about the mechanistic details of the Ca2+ ion impact and the Ca2+ binding capabilities of PAF outside the fungal cell, which might be the reason for the activity loss. Using nuclear magnetic resonance (NMR), isothermal titration calorimetry and molecular dynamics (MD) simulations we demonstrated that PAF weakly, but specifically binds Ca2+ ions. MD simulations of PAF predicted one major Ca2+ binding site at the C-terminus involving Asp53 and Asp55, while Asp19 was considered as putative Ca2+ binding site. The exchange of Asp19 to serine had little impact on the Ca2+ binding, however caused the loss of antifungal activity, as was shown in our recent study. Now we replaced the C-terminal aspartates and expressed the serine variant PAFD53S/D55S. The specific Ca2+ binding affinity of PAFD53S/D55S decreased significantly if compared to PAF, whereas the antifungal activity was retained. To understand more details of Ca2+ interactions, we investigated the NMR and MD structure/dynamics of the free and Ca2+-bound PAF and PAFD53S/D55S. Though we found some differences between these protein variants and the Ca2+ complexes, these effects cannot explain the observed Ca2+ influence. In conclusion, PAF binds Ca2+ ions selectively at the C-terminus; however, this Ca2+ binding does not seem to play a direct role in the previously documented modulation of the antifungal activity of PAF.